1992
DOI: 10.1063/1.106508
|View full text |Cite
|
Sign up to set email alerts
|

High critical-current densities in (Tl0.5Pb0.5)Sr2Ca2Cu3O9 with T c up to 115 K

Abstract: A high critical-current density was observed in the material (Tl0.5Pb0.5)Sr2Ca2Cu3O9. Based on magnetic-hysteresis measurements, this single (insulating) Tl-O layer material has a Jc value of 1.24×105 A/cm2 when measured at a temperature of 77 K and a field of 1 T. This value of Jc is comparable to that measured here for YBa2Cu3O7 (1.04×105 A/cm2), having single-conducting Cu-O chains, but considerably greater than the value for the material Tl2Ba2Ca2Cu3O10 with double (insulating) Tl-O layers in which no hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…This phase line actually separates the phase diagram into zero and finite resistive dissipation. In the cuprate family, some compounds of the Bi-based ( 1 ), Hg-based ( 2 ), and Tl-based ( 3 ) systems show superconducting transition temperatures beyond 100 K. Among all these materials, it was reported that the (Tl 0.5 Pb 0.5 )Sr 2 Ca 2 Cu 3 O 9 [(Tl,Pb)-1223] ( 4 , 5 ) exhibits a rather high irreversibility line with an irreversibility field of nearly 10 T at the liquid nitrogen boiling temperature (~77 K), which is thought to be promising for applications. However, for Hg- and Tl-based systems, the toxic elements Hg and Tl strongly limit the high-power applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…This phase line actually separates the phase diagram into zero and finite resistive dissipation. In the cuprate family, some compounds of the Bi-based ( 1 ), Hg-based ( 2 ), and Tl-based ( 3 ) systems show superconducting transition temperatures beyond 100 K. Among all these materials, it was reported that the (Tl 0.5 Pb 0.5 )Sr 2 Ca 2 Cu 3 O 9 [(Tl,Pb)-1223] ( 4 , 5 ) exhibits a rather high irreversibility line with an irreversibility field of nearly 10 T at the liquid nitrogen boiling temperature (~77 K), which is thought to be promising for applications. However, for Hg- and Tl-based systems, the toxic elements Hg and Tl strongly limit the high-power applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Tl-1223 superconductors have been found to have higher J c as compared to Tl-2212 and Tl-2223 compounds [47,49,50]. The Tl-1223 superconductors are very useful in electronic devices fabrication because the critical currents in these compounds decreases slowly as compared to double Tl-O layer compounds in the presence of external magnetic fields [47,55]. In Figure 12, a comparison of the magnetic field dependence of J c (77K) of Tl-1223 and Tl-2212 is shown.…”
Section: Why Tl-1223 Superconductor Is Superiormentioning
confidence: 99%
“…These superconducting compounds are more promising because of their lower anisotropy, higher T c (0), higher critical current densities and irreversibility field H irr as compared to their counterparts in double Tl-O layer superconductors family [47][48][49][50][51][52][53][54][55]. The TlSr 2 CaCu 2 O 7 (Tl-1212) is the parent compound in single Tl-O layer superconductors showing no signs of superconductivity down to liquid helium temperature because it grows in the over-doped state [56].…”
Section: Tl 1 Ba 2 Ca N-1 Cu N O 2n+2 Superconductorsmentioning
confidence: 99%
“…The single Tl-O layer compounds have primitive tetragonal structure. The higher superconducting properties of single layer thallium-based compounds make them preferable over double layer thallium-based compounds [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can be generally represented by Tl-22(n − 1)n, where "n" represents the number of CuO 2 planes. On the other hand, the monolayer Tl-based system includes TlBa 2 [6][7][8][9][10][11][12][13][14]. The single Tl-O layer compounds have primitive tetragonal structure.…”
Section: Introductionmentioning
confidence: 99%